STRENGTHENING MATERNAL AND CHILD HEALTH SYSTEM TOWARDS INDONESIA EMAS 2045 - Rahvy, Aisyah Putri (Universitas Airlangga, 2025)
This editorial article highlights the important role of strengthening the maternal and child health system for the overall increase of the nation’s productivity, as well as the achievement of Indonesia Emas 2045. The discussion emphasized accessibility of maternal health services in community health services like Posyandu through readiness of health cadres, especially after the government implemented Integrated Primary Health Services or Integrasi Layanan Primer (ILP). Moreover, the implementation of exclusive breastfeeding was found to be significantly associated with stunting, making it a pivotal program to decrease stunting prevalence and increase infants’ health quality. Although some challenges like geographic barriers, limitation of knowledge and education, as well as low household income existed, investing in the maternal and child health system would solve the problem of the high mortality rate among mothers and infants. As Indonesia Emas 2045 was set as national development goals, the article stands up for better quality of maternal and child health in Indonesia through collaboration across sectors with an inclusive decision-making process. Keywords: Child health, health system, infant health, maternal health.